HBR's 10 Must Reads on Change Management, Vol. 2 - Review, Harvard (Ascent Audio, 2021)
Lead change amid constant turbulence and disruption. More of the ideas you want, from the authors you trust. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you spearhead change in your organization. With insights from leading experts including John Kotter and Indra Nooyi, this book will inspire you to: lead through the eight critical stages of change; create and instill a sense of urgency; transform your company's culture; get reorgs right; reshape your organization for climate sustainability; remodel the chief learning officer position to lead change; scale agile practices throughout your organization; and lead change when business is good-but also when times are tough.